THE EFFECT OF TRAINING SATISFACTION, PERFORMANCE APPRAISAL SATISFACTION, AND EMPLOYEE SALARY SATISFACTION ON TURNOVER INTENTION AT PT. KAI COMMUTER (CASE STUDY AT UNIVERSITY OF INDONESIA STATION) - Putri Harijanto, Nafisah Mega; Sadikin, Mochammad Rizki (International Humanities and Applied Science Journal, 2025)
This quantitative study, using a descriptive design, explores how satisfaction with training, performance appraisal, and salary influences turnover intention. Data were collected through a survey using a questionnaire as the research instrument. The population comprised 50 contract employees of PT. KAI Commuter stationed at the University of Indonesia, and the sample was a saturated group of the same 50 contract staff. Instrument, validity, and reliability tests were applied for data analysis, while data processing employed Structural Equation Modeling (SEM) with the Partial Least Squares (PLS) method. Findings revealed that satisfaction with training, performance appraisal, and salary each exerted a negative and significant influence on turnover intention.